2012
DOI: 10.1016/j.bpj.2012.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Intermediate Filament Networks Assembled from Keratin 8 and 18 in the Presence of Mg2+

Abstract: The mechanical properties of epithelial cells are modulated by structural changes in keratin intermediate filament networks. To investigate the relationship between network architecture and viscoelasticity, we assembled keratin filaments from recombinant keratin proteins 8 (K8) and 18 (K18) in the presence of divalent ions (Mg(2+)). We probed the viscoelastic modulus of the network by tracking the movement of microspheres embedded in the network during assembly, and studied the network architecture using scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 61 publications
4
49
0
Order By: Relevance
“…Similar effect can be expected for keratin and structural differences might play a role, that can be accessed with X-rays. Furthermore, it has been shown that Mg 2+ ions are cross-linking keratin filaments [103,190,191] or other IFs [187,233]. Very similar conclusion can be drawn from the micro-diffraction measurements.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…Similar effect can be expected for keratin and structural differences might play a role, that can be accessed with X-rays. Furthermore, it has been shown that Mg 2+ ions are cross-linking keratin filaments [103,190,191] or other IFs [187,233]. Very similar conclusion can be drawn from the micro-diffraction measurements.…”
Section: Resultssupporting
confidence: 67%
“…Here, the following assumptions have been applied: i) the Gaussian chains are located at the rod surface, ii) the number of Gaussian chains corresponds to 16 monomers per ULF length (about 43 nm), thus λ = 2.69 nm, iii) the standard deviation of the filament thickness distribution is estimated to 17.02% of the average radius [114] and iv) the persistence length of about 500 nm for keratin [103] is much larger than the length scale accessible by SAXS, which corresponds to about 60 nm. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2) already show an influence of 10 mM KCl on network mechanics, which is below the bundling onset concentration. The same gradual change in network mechanics was reported by Leitner et al 29 for MgCl 2 . Here also concentrations clearly below the onset concentration were sufficient to alter network mechanics.…”
Section: Discussionsupporting
confidence: 64%